Interaction between Phosphate Solubilizing Bacteria and Arbuscular Mycorrhizal Fungi on Growth Promotion and Tuber Inulin Content of Helianthus tuberosus L - Nacoon, Sabaiporn; Jogloy, Sanun; Riddech, Nuntavun; Mongkolthanaruk, Wiyada; Kuyper, Thomas W.; Boonlue, Sophon (Scientific reports, 2020)
Arbuscular mycorrhizal fungi (AMF) and phosphate solubilizing bacteria (PSB) could interact synergistically because PSB solubilize sparingly available phosphorous compounds into orthophosphate that AMF can absorb and transport to the host plant. Little is known about the interactions between these two groups in terms of promoting Jerusalem artichoke, Helianthus tuberosus L., which is widely planted by farmers because of its high inulin content. Production depends mainly on synthetic fertilizers as source of plant nutrients. This study aimed to isolate and characterize PSB and investigate the effects of co-inoculation of AMF and PSB on plant performance and inulin accumulation. Isolate UDJA102x89-9, identified as Klebsiella variicola (KV), showed phosphate-solubilizing ability and produced high amounts of several organic acids in vitro and of indole-3-acetic acid (IAA). The experiment combined KV and two AMF species ( Glomus multisubtensum (GM) and Rhizophagus intraradices (RI)). Co-inoculation of KV with RI, in combination with rock phosphate, showed the largest increases in plant growth and tuber inulin content, compared both to an unfertilized and fertilized control. This result would reveal whether the phosphate solubilization and IAA property of the PSB in vitro played a significant role in changing plant growth and production, and the available P was subsequently taken up and transported to plant roots by AMF. The high combined effect may have the potential for use by farmers in the future as a biofertilizer for inulin production by Helianthus tuberosus L.